Towards a multidimensional model of Specific Language Impairment and Dyslexia: Shared and specific deficits - Acha, Joana (Revista de Investigación en Logopedia, 2016)
This article reviews the nature and relationships among basic processes involved in Specific Language Impairment (SLI) and reading impairment (dyslexia), based on the DSM-V classification criteria. SLI implies difficulties for the perception and discrimination of speech sounds, acquisition of vocabulary, as well as for the understanding and production of language and grammar rules. Dyslexia is included within learning impairments, and it involves a difficulty in the acquisition of mapping rules between letters and their corresponding sounds as well as fluent reading. Both impairments are classified as independent categories and its possible interdependence is not well defined. Recent investigations have demonstrated a shared deficit of phonological nature, which can be defined around two different although interrelated dimensions: the ability to create phonological representations and the ability to process and retrieve them from memory. It has also been observed that both impairments imply limitations at other cognitive levels such as attention, working memory, and processing speed. This fact could explain the high comorbidity rate between language, reading and attention impairments. These findings emphasize the continuity of the deficits and the multidimensional nature of impairments, and pose a challenge for the categorical perspective of traditional classification methods. New research devoted to highlight common causes and specific features of these disorders will allow detecting early at risk markers, with clear implications for future evaluation and treatment.
Keywords: Attention; Comorbidity; Language and reading; Phonological deficit; Phonological representations; Working memory.